2016
DOI: 10.1155/2016/5409653
|View full text |Cite
|
Sign up to set email alerts
|

Presence of DQ2.2 Associated with DQ2.5 Increases the Risk for Celiac Disease

Abstract: Background. Celiac disease (CD) is a genetically determined immune-mediated disorder in which gluten immunogenic peptides are presented to CD4 T cells by HLA-DQ2.5, DQ8, DQ2.2, and their combinations. Our aim is to establish a risk gradient for celiac disease based on HLA-DQ profile in a brazilian representative population and the relevance of DQ2.2 in celiac disease development. Materials and Methods. 237 celiac patients and 237 controls (both groups with 164 females and 73 males) were included. All samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
3
20
1
7
Order By: Relevance
“…13‐17 However, the highest risk for CD in these studies was associated with homozygous HLA‐DQ2.5 and DQ2.5/DQ2.2 , while DQ2.5/DQ8 was associated with an intermediate risk. Previous studies reported an intermediate/high risk of develop CD in individuals carrying DQ8 ; however, in our study, individuals carrying DQ8 had a risk similar to that of the general population (1:70; OR: 0.700). Values that were lower than the CD prevalence in the general Saudi population were demonstrated for the DQ2.2 genotype (1:241), which was associated with an intermediate or high risk in other populations .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…13‐17 However, the highest risk for CD in these studies was associated with homozygous HLA‐DQ2.5 and DQ2.5/DQ2.2 , while DQ2.5/DQ8 was associated with an intermediate risk. Previous studies reported an intermediate/high risk of develop CD in individuals carrying DQ8 ; however, in our study, individuals carrying DQ8 had a risk similar to that of the general population (1:70; OR: 0.700). Values that were lower than the CD prevalence in the general Saudi population were demonstrated for the DQ2.2 genotype (1:241), which was associated with an intermediate or high risk in other populations .…”
Section: Discussioncontrasting
confidence: 84%
“…The HLA‐DQ2.2 genotype has infrequently been reported in previous studies, which might be explained by the true rarity of this genotype in some populations, such as Finnish patients with CD, or incomplete HLA typing. In recent studies a similar prevalence of HLA‐DQ2.2 (but not HLA‐DQ2.5 or HLA‐DQ8 ) (3.6%‐5.8%) in patients with CD has been reported in different ethnicities which suggests that incomplete HLA typing may be the most likely cause for the missing HLA‐DQ2.2 haplotype in previous studies. A minority of celiac patients (<1%) carry a single allele of the HLA‐DQ2.5 heterodimer: HLA‐DQA1*05 or HLA‐DQB1*02 , known as half‐heterodimers .…”
Section: Discussionmentioning
confidence: 99%
“…Even though this kind of molecule does not bind as efficient as DQ2.5 to gluten peptides, it does strong enough to build up a T‐cell antigluten response, leading to the development of CD (Bodd, Kim, Lundin, & Sollid, ). A previous study performed by our group confirmed the relevance of this genetic variant in the Brazilian population (Almeida et al., ).…”
Section: Discussionsupporting
confidence: 80%
“…According to recent studies the most prevalent haplotype found in patients lacking HLA-DQ2.5 and HLA-DQ8 is HLA-DQ2.2 (Mubarak et al, 2013). However, previous studies performed in a smaller Brazilian population sample suggest that HLA-DQ2.2 can only be considered a risk factor when associated with DQ2.5 (Almeida et al, 2016;Selleski et al, 2018).These variants are responsible for only 40% of the genetic risk of CD and are carried by approximately 30% of the general Caucasian population (Megiorni & Pizzuti, 2012), thus suggesting that HLA is only one of the regions that could confer risk of developing this condition. However, the other 60% of the genetic susceptibility to CD is shared by HLA class I and non-HLA genes, each of which is estimated to contribute only with a small risk effect (Trynka et al, 2011;Withoff, Li, Jonkers, & Wijmenga, 2016).…”
mentioning
confidence: 99%
“…Approximately 93% of CD patients will carry HLA-DQ2 or HLA-DQ8. 22,23 It depends on the study. Some say 95%.…”
mentioning
confidence: 99%